Easily-sintered light high-strength steel powder as well as preparation method and application thereof
By doping elements such as Nb, Cu, Sc in Fe-Al-Mn-C lightweight high-strength steel, the instantaneous liquid phase and nitride are formed, the problem of difficulty in sintering of lightweight high-strength steel is solved, the sintering temperature range is expanded and the density and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202411982637.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
Fe-Al-Mn-C lightweight high-strength steel is difficult to sinter, and the sintering temperature range is narrow, making it difficult to obtain high-density and high-performance lightweight steel.
By doping elements such as Nb, Cu, Sc, etc., a transient liquid phase is formed to promote sintering, reduce the melting point of the alloy, and improve contact conditions and densification during the sintering process through the formation of nitride and copper.
The sintering temperature range of lightweight high-strength steel is expanded so that it can be sintered between 1160-1250℃ to obtain dense lightweight high-strength steel, which improves the density and mechanical properties of the material.
Smart Images

Figure CN119710471A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of light-weight high-strength steel powder preparation, and in particular relates to an easy-to-sinter light-weight high-strength steel powder and a preparation method and application thereof. Background Art
[0002] Lightweight steel is Fe-Al or Fe-Mn-Al-C alloy steel formed by adding Al element to ultra-low carbon steel or C-Mn steel. Among them, Fe-Al-Mn-C steel is often used as energy-saving and environmentally friendly structural materials and widely used in light construction industry or transportation system due to its advantages of low density, high strength, and good mechanical properties at room temperature or low temperature. Powder metallurgy technology is a process technology that uses metal powder or non-metallic powder mixture as raw material to manufacture various metal materials, composite materials and products through forming and sintering processes. Through powder metallurgy technology, we can obtain specific chemical composition and mechanical and physical properties that are difficult to achieve by traditional melting and casting methods, and directly prepare porous, semi-dense or fully dense materials. In the mass production of complex lightweight steel parts, powder metallurgy technology, especially injection molding or compression molding technology, has played a vital role, which not only improves production efficiency and ensures product quality, but also reduces production costs.
[0003] In iron-based materials, since there is generally a passivation film on the surface of Fe powder, significant reduction can only occur at a temperature above 1150°C, otherwise it will hinder the diffusion of atoms during sintering. Usually, it is difficult to obtain high density when powder metallurgy steel is sintered below 1250°C. However, in lightweight high-strength steel composed of Fe-Al-Mn-C, the melting point of Al is only 660°C, and the melting point of Mn is 1246°C. The addition of both reduces the melting point of the material, causing the powder to quickly undergo liquid phase sintering. Excessive liquid phase will lead to significant grain growth and overburning, and the loss of liquid phase will form holes, causing obvious sintering defects; while Mn has a low vapor pressure and is easy to volatilize; C increases the tendency of significant grain growth. On the other hand, Al oxide is very stable, which will increase the difficulty of reducing the surface passivation film. This series of reasons make it difficult to sinter Fe-Al-Mn-C lightweight high-strength steel: if the sintering temperature is too low, more holes will be formed inside the material, making it difficult to obtain high-density, high-performance lightweight steel; if the sintering temperature is too high, too much liquid phase will be formed during the sintering process, causing grain growth, local liquid phase loss will also produce holes, and segregation may occur. As a result, the sintering temperature range of lightweight steel is narrow, and generally only sintering between 1210-1250℃ can achieve better performance, which puts extremely high demands on temperature field control and temperature fluctuation in sintering engineering.
[0004] Based on the above reasons, it is urgent to open up new lightweight and high-strength steel composition ratios. This can be achieved by doping other alloy elements, such as Cr, Ni, etc., but Cr doping is harmful to performance, and Ni doping will further increase the sintering temperature. Summary of the invention
[0005] In view of the shortcomings of the existing Fe-Al-Mn-C lightweight steel powder metallurgy technology, the first purpose of the present invention is to provide an easily sintered lightweight high-strength steel powder. The easily sintered lightweight high-strength steel powder provided by the present invention has a sintering range of 1160-1250°C, which is greatly widened compared with the sintering range of the prior art.
[0006] The second object of the present invention is to provide a method for preparing light and high-strength steel powder that is easy to sinter.
[0007] The third object of the present invention is to provide an application of easy-to-sinter lightweight high-strength steel powder.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The invention discloses an easy-to-sinter light high-strength steel powder. The easy-to-sinter light high-strength steel powder has the following components by mass percentage: C 0.6-2wt.%, Mn 28-32wt.%, Al 9-14wt.%, Nb 0.01-0.6wt.%, Cu: 0.01-0.6wt.%, Sc 0.1-0.5wt.%, N 0.1-0.3wt.%, and the balance is Fe.
[0010] The present invention provides an easy-to-sinter lightweight high-strength steel powder, which is doped with appropriate amounts of Nb, Cu and Sc; wherein the eutectic liquid phase temperature of Nb and Fe is 1360°C, and the eutectic liquid phase temperature of Mn is 1224°C, which can reduce the melting point of the alloy, but the formed liquid phase is a transient liquid phase, that is, it can be quickly absorbed by the solid phase and will not form a stable liquid phase. Although the transient liquid phase exists for a short time, the formation and spread of the liquid phase will have a cracking effect on the oxide film during diffusion bonding. Secondly, the transient liquid phase can reduce the generation of brittle phases such as intermetallic compounds. In addition, instantaneous liquid phase diffusion bonding also has the advantages of low bonding temperature, no heat affected zone and small residual stress. In addition, the addition of Nb also generates NbC with C in the alloy. This phase is very stable at the sintering temperature, which can inhibit grain growth and is generally spherical at the micron level, rather than a network of chromium carbides precipitated along the grain boundary, with a more excellent strengthening effect. The addition of an appropriate amount of Cu generates liquid phase copper during the sintering process. Liquid phase Cu can wet the metal surface, improve the contact conditions during the sintering process, and promote the rearrangement and densification between particles. The addition of Sc is conducive to absorbing oxygen in the alloy, reducing the resistance of sintering, improving the sintering efficiency, and helping to ensure the uniformity of the alloy and prevent the occurrence of segregation. In addition, the nitrogen contained in the powder combines with aluminum to form aluminum nitride. Compared with aluminum oxide, aluminum nitride has a loose structure and is easy to break during the sintering process, which can expose a fresh surface to bond with other metal atoms. Aluminum oxide is very stable, which hinders atomic bonding during the sintering process, thereby hindering sintering densification. Through the synergistic effect of the above elements, the sintering temperature range of Fe-Al-Mn-C lightweight steel is doubled from 30-40 degrees to 80-90 degrees.
[0011] However, the amount of added elements needs to be effectively controlled. If too much Nb is added, the sintering performance of the alloy will be reduced. Too much Nb may form too many carbides NbC. Although these carbides can inhibit grain growth and increase strength to a certain extent, too many carbides may cause the powder to be difficult to densify during the sintering process, forming holes and cracks. And too much Nb content will increase the melting point of the alloy, so that the sintering temperature needs to be further increased, thereby increasing the difficulty and cost of the sintering process. Secondly, excessive Nb will also generate too much hard phase, resulting in reduced toughness of the alloy and increased risk of brittle fracture. Sc is a relatively rare metal element with high cost. Too much Sc will increase the manufacturing cost of the alloy. And although Sc is conducive to absorbing oxygen in the alloy and reducing sintering resistance, too much Sc may easily segregate and form an uneven structure, affecting the performance of the alloy. If too little Sc is added, it may not be able to fully play its role in absorbing oxygen, reducing sintering resistance and ensuring alloy uniformity, thus affecting the sintering effect and alloy properties. If too much Cu is added, it will cause too much liquid phase to be formed during the sintering process, thereby causing significant growth of grains and reducing the mechanical properties of the material. Excessive liquid phase will also lead to liquid phase loss, forming holes and sintering defects, affecting the density and performance of the material. The right amount of Cu can promote particle rearrangement and sintering densification, but if too little Cu is added, Cu cannot provide enough liquid phase to promote the sintering process, resulting in poor sintering effect.
[0012] Preferably, the easily sintered lightweight high-strength steel powder is prepared by a gas atomization method.
[0013] In a preferred embodiment, the particle size D of the sinterable lightweight high-strength steel powder is 10 =3-6μm, D 50 =10-14μm, D 90 =22-30μm.
[0014] It can be seen that the particle size of the easily sintered lightweight high-strength steel powder provided by the present invention is small, uniform, and narrowly distributed.
[0015] The invention discloses a method for preparing an easily sintered light high-strength steel powder. The method comprises the following steps: mixing various raw materials according to the designed proportion of the easily sintered light high-strength steel powder, smelting to obtain a high-strength steel alloy liquid, continuously heating the high-strength steel alloy liquid to superheat it, and then performing a gas atomization treatment to obtain the light high-strength steel powder.
[0016] The preferred solution is to prepare carbon powder, pure manganese, pure aluminum, pure niobium and pure iron according to the design ratio of the easy-to-sinter lightweight high-strength steel powder, and smelt to obtain alloy liquid 1, wherein the carbon powder content of the alloy liquid 1 is 0.6-2wt.%, the pure manganese content is 28-32wt.%, the pure aluminum content is 9-14wt.%, the pure niobium content is 0.01-0.6wt.%, and the balance is pure iron; prepare ferromanganese nitride, copper nitride, pure niobium, aluminum-scandium alloy and pure iron, and smelt to obtain alloy liquid 2, wherein the ferromanganese nitride content of the alloy liquid 2 is 1-5wt.%, the copper nitride content is 0.1-3wt.%, the pure niobium content is 0.01-0.6wt.%, the aluminum-scandium alloy content is 0.1-1wt.%, and the balance is pure iron; take out 1 / 3 of the volume of the alloy liquid 1, then take the alloy liquid 2 equal to the alloy liquid 1, pour it into the remaining alloy liquid 1, and continue to refine to form a high-strength steel alloy liquid.
[0017] In the present invention, the above-mentioned smelting method is adopted to ensure that all elements are fully dissolved and evenly distributed. If the above-mentioned method is not followed and the smelting is carried out in a manner of separating the alloy liquid 1 and the alloy liquid 2, problems such as uneven composition and decreased alloy performance may be caused. In particular, when nitrogen-containing compounds such as ferromanganese nitride and copper nitride are added, if the smelting method of the present invention is not followed, they may undergo complex reactions with other elements in the alloy, affecting the composition and structure of the alloy.
[0018] The preparation method of the present invention, in the smelting process, the alloy liquid 2 replaces 1 / 3 of the original corresponding component alloy liquid 1. The Sc content is 0.1-0.5wt.%, and the corresponding nitrogen is used as the protective gas for atomization. The obtained powder finally contains 0.1-0.3wt.% of nitrogen, which is evenly distributed on the surface of the powder. In addition to increasing the nitrogen content, the manganese element in the manganese ferronitride is also an important component of the alloy, which has a synergistic enhancement effect on the performance of the alloy. Copper nitride, at the sintering temperature, can be partially decomposed to obtain a small amount of liquid phase copper. The liquid phase Cu can wet the metal surface, improve the contact conditions during the sintering process, promote the rearrangement and densification between particles, and further promote sintering densification; Scandium is added in the form of aluminum-scandium alloy to better ensure the uniformity of the addition. During the sintering process, nitrogen combines with aluminum to form aluminum nitride. Compared with aluminum oxide, the aluminum nitride has a loose structure and is easy to break during the sintering process, which can expose a fresh surface to achieve bonding with other metal atoms. Aluminum oxide is very stable and hinders atomic bonding during the sintering process, thereby hindering sintering densification. As a result, the easily sintered lightweight high-strength steel powder of the present invention can be sintered in a wider sintering range to obtain dense lightweight high-strength steel.
[0019] In a preferred embodiment, the refining is carried out under electromagnetic stirring for 0.5-1 h. Refining under electromagnetic stirring for 0.5-1 h can ensure that all elements are fully dissolved and evenly distributed.
[0020] According to a preferred solution, the high-strength steel alloy liquid is superheated to 60-250°C and then subjected to gas atomization treatment.
[0021] In the actual operation process, the raw materials are loaded into a ceramic crucible in a vacuum induction melting furnace, the ceramic crucible is gradually heated and then kept warm until the raw materials are completely melted to obtain alloy liquid 1 and alloy liquid 2 respectively. After mixing, the alloy liquid is obtained after electromagnetic stirring for 0.5-1h; the vacuum induction melting furnace is filled with protective gas to ensure that the vacuum induction melting furnace is in a slightly positive pressure state; the temperature of the master alloy melt is detected by an infrared temperature measuring instrument, and when the superheat of the alloy melt reaches between 60-250°C, the alloy melt is downwardly discharged through the guide nozzle under the ceramic crucible; under the condition of an air pressure of 5-25, a high-pressure N2 flow is passed through a nozzle to atomize the alloy melt and break it into a large number of fine droplets, and alloy powder is obtained after solidification.
[0022] Preferably, the pressure of the aerosol treatment is 5-20 MPa.
[0023] In a preferred embodiment, the alloy powder obtained after gas atomization treatment is sieved and then dried at 100-120° C. for 1-3 hours to obtain a lightweight high-strength steel powder.
[0024] The invention discloses an application of an easy-to-sinter light-weight high-strength steel powder, and uses the easy-to-sinter light-weight high-strength steel powder as a raw material to prepare light-weight high-strength steel.
[0025] According to a preferred embodiment, the preparation process of the lightweight high-strength steel is as follows: mixing an easily sintered lightweight high-strength steel powder with a binder to obtain a feed material, performing injection molding of the feed material to obtain a rough blank, catalytically degreasing the rough blank to obtain a degreased blank, and sintering the degreased blank to obtain a lightweight high-strength steel. The sintering temperature is 1160-1250°C, and the sintering time is 5-10h.
[0026] Further preferably, the binder comprises the following ingredients by mass percentage: 85-89% polyoxymethylene (POM), 3-8% polyethylene (PE), 1-6% ethylene-vinyl acetate copolymer (EVA), 1-2% polyethylene wax (PE wax), 2-7% carnauba wax (CW), 1-3% styrene-acrylonitrile copolymer (SA), and 0.1-1% antioxidant (B215). The binder formula combines a variety of different types of polymers and additives to achieve specific performance requirements, and is not a "conventional" binder in the traditional sense. Polyethylene (PE) provides basic strength and toughness. The addition of ethylene-vinyl acetate copolymer (EVA) is to increase softness, elasticity and transparency, while improving the flexibility and low temperature resistance of the binder. Wax components (such as PE wax, CW) are also added to this plastic-based binder to improve the processing properties of the mixture and the surface properties of the final product. The addition of styrene-acrylonitrile copolymer (SAN) improves hardness, heat resistance and chemical resistance, and also enhances the strength and durability of the adhesive. The addition of antioxidant B215 can prevent the adhesive from degradation due to oxidation during processing and use, thus extending its service life.
[0027] Further preferably, the injection molding temperature is 170-180° C. and the pressure is 80-90 MPa.
[0028] Further preferably, the catalytic degreasing is carried out in an atmosphere of fuming nitric acid, the temperature of the catalytic degreasing is 100-140° C., and the time of the catalytic degreasing is 3-8 hours.
[0029] In actual operation, the degreased blank obtained after catalytic degreasing is filled with inert gas Ar and sintered to obtain lightweight and high-strength steel.
[0030] Further preferably, the density of the lightweight high-strength steel is 6.35-6.50 g / cm 3 , tensile strength is 970-1040, yield strength is 840-880, elongation is 8.8-11.5%, and hardness is 26-29HRC.
[0031] Principles and advantages
[0032] The present invention provides an easy-to-sinter lightweight high-strength steel powder. The present invention adds Nb to the lightweight high-strength steel. The eutectic liquid phase temperature of Nb and Fe is 1360°C, and the eutectic liquid phase temperature of Mn is 1224°C. The melting point of the alloy can also be reduced, but the formed liquid phase can be quickly absorbed by the solid phase and will not form a stable liquid phase. Although the transient liquid phase exists for a short time, the formation and spread of the liquid phase will have a cracking effect on the oxide film in the diffusion connection. Secondly, the transient liquid phase can reduce the generation of brittle phases such as intermetallic compounds. In addition, the transient liquid phase diffusion connection also has the advantages of low connection temperature, no heat-affected zone, and small residual stress. The addition of Nb also generates NbC with C in the alloy. This phase is very stable at the sintering temperature, can inhibit grain growth, and is generally micron-sized spherical, rather than a network of chromium carbides precipitated along the grain boundary, and the strengthening effect is more excellent.
[0033] In addition, the present invention adopts the addition of ferromanganese nitride, copper nitride, and niobium to the raw materials, and adopts the corresponding nitrogen as the protective gas for atomization, and the obtained powder finally contains 0.1-0.3wt.% nitrogen, which is evenly distributed on the surface of the powder. During the sintering process, nitrogen combines with aluminum to form aluminum nitride. Compared with aluminum oxide, the aluminum nitride has a loose structure and is easy to break during the sintering process, which can expose a fresh surface to bond with other metal atoms. Aluminum oxide is very stable, which hinders atomic bonding during the sintering process, thereby hindering sintering densification. In addition, copper nitride can be partially decomposed at the sintering temperature to obtain a small amount of liquid copper, which can wet the metal and promote particle rearrangement. Sc is conducive to absorbing oxygen in the alloy, reducing the resistance of sintering, and is not easy to be segregated, ensuring the uniformity of the alloy. Through the mutual promotion of several effects, the sintering temperature range of the previous Fe-Al-Mn-C lightweight steel can be doubled from 30-40 degrees to 80-90 degrees.
[0034] Therefore, the lightweight high-strength steel material prepared by the easy-to-sinter lightweight steel powder provided by the present invention has the advantages of high density, excellent mechanical properties, easy sintering, etc., because nitride promotes atomic bonding, copper promotes sintering diffusion, and Sc is beneficial to absorb oxygen. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Scanning electron microscope image of the lightweight high-strength steel prepared in Example 1, the white round micron-sized particles in the image are NbC.
[0036] Figure 2 Scanning electron microscope image of the lightweight high-strength steel prepared in Example 2, the white round micron-sized particles in the image are NbC.
[0037] Figure 3 Scanning electron microscope image of the lightweight high-strength steel prepared in Comparative Example 4.
[0038] Figure 4 Scanning electron microscope image of the lightweight high-strength steel prepared in Comparative Example 5. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.
[0040] Example 1
[0041] A method for preparing a sinterable lightweight high-strength steel powder. The lightweight steel is prepared according to an optimal value range. The prepared lightweight steel contains, by mass percentage, the following: Mn: 31.82wt.%, Al: 9.75wt.%, C: 1.84wt.%, Nb: 0.30wt.%, N: 0.21wt.%, Cu: 0.2wt.%, Sc: 0.26wt.%, O: 0.018wt.%, S: 0.012wt.%, and the balance is Fe.
[0042] A method for preparing a sinterable lightweight high-strength steel powder, wherein the lightweight high-strength steel powder is prepared by a gas atomization method, and the product is obtained through a series of treatments such as mixed material smelting, gas atomization powder making, powder drying, adding a plastic-based binder, injection molding and post-processing.
[0043] The process of mixing, melting, atomizing and powdering, and drying the powder is as follows:
[0044] Carbon powder, pure manganese, pure aluminum, pure niobium, and pure iron are prepared, with a C content of 1.84wt.%, a Mn content of 31.82wt.%, an Al content of 9.75wt.%, a Nb content of 0.30wt.%, and the balance of Fe, and are placed in a ceramic crucible in a vacuum induction melting furnace to obtain alloy liquid 1. In addition, ferromanganese nitride, copper nitride, pure niobium, aluminum-scandium alloy, and pure iron are prepared, with a ferromanganese nitride content of 3wt.%, a copper nitride content of 2wt.%, a niobium content of 0.30wt.%, and an aluminum-scandium alloy content of 0.52wt.%, and the balance of Fe, and are placed in a ceramic crucible in a vacuum induction melting furnace to obtain alloy liquid 2. 1 / 3 of alloy liquid 1 is taken out and an equal amount of alloy liquid 2 is poured in, so that alloy liquid 2 replaces 1 / 3 of the original alloy liquid 1 of the corresponding component. The Sc content is set to 0.26wt.%, and the electromagnetic stirring is continued for 1h to obtain the alloy melt; the protective gas is filled into the vacuum induction melting furnace to ensure that the vacuum induction melting furnace is in a slightly positive pressure state; the temperature of the master alloy melt is detected by an infrared temperature measuring instrument, and when the superheat of the alloy melt reaches 150°C, the alloy melt flows downward through the guide nozzle under the ceramic crucible; under the condition of an air pressure of 15, the high-pressure N2 flow is passed through the nozzle to atomize and break the alloy melt into a large number of fine droplets, and the alloy powder is obtained after solidification. After atomization, 0.21wt.% of nitrogen is obtained, and the obtained light high-strength steel powder is sieved, and the sieved light high-strength steel powder is dried in a heating furnace at 110°C for 2h.
[0045] A method for preparing a light and high-strength steel powder that is easy to sinter, wherein the powder is prepared by a gas atomization method, and the obtained powder particle size is D 10 =4.51μm, D 50 =12.55μm, D 90 =26.16μm.
[0046] The process of adding plastic-based binder, injection molding and post-processing is as follows:
[0047] The feed is obtained by mixing the binder of the sinterable light high-strength steel powder, wherein the binder, by mass ratio, has the following composition: polyoxymethylene (POM) 87.5%, polyethylene (PE) 5%, ethylene-vinyl acetate copolymer (EVA) 1%, polyethylene wax (PE wax) 1%, carnauba wax (CW) 2%, styrene-acrylonitrile copolymer (SA) 3%, antioxidant (B215) 0.5%; then the injection blank is stretched at an injection temperature of 175°C and a pressure of 85; the binder is removed from the injection blank by a two-step degreasing method, the injection blank is first catalytically degreased, the sample is evenly placed in a catalytic degreasing furnace, and the degreasing is carried out in a fuming nitric acid atmosphere, the degreasing temperature is 120°C, and the time is 5h; then the degreased injection blank is loaded into a vacuum sintering furnace and filled with inert gas Ar.
[0048] A method for preparing an easily sintered light-weight high-strength steel powder. The sintering conditions of the light-weight high-strength steel powder are as follows: sintering at 1200° C. for 8 hours and then cooling in a furnace to obtain an alloy blank, namely, the light-weight high-strength steel.
[0049] Example 2
[0050] The other conditions were the same as those in Example 1, except that the sintering temperature was 1160°C.
[0051] Example 3
[0052] The other conditions were the same as those in Example 1, except that the sintering temperature was 1250°C.
[0053] Example 4
[0054] The other conditions were the same as those in Example 1, except that the Nb content was 0.2 wt.%.
[0055] Example 5
[0056] The other conditions were the same as those in Example 1, except that the Nb content was 0.5 wt.%.
[0057] Comparative Example 1
[0058] The other conditions were the same as those in Example 1, except that the Nb content was 1 wt.%.
[0059] Comparative Example 2
[0060] The other conditions were the same as those in Example 1, except that Nb was not added and the sintering temperature was increased to 1160°C.
[0061] Comparative Example 3
[0062] The other conditions were the same as those in Example 1, except that Nb was not added and the sintering temperature was increased to 1200°C.
[0063] Comparative Example 4
[0064] The other conditions were the same as those in Example 1, except that Nb was not added and the sintering temperature was increased to 1250°C.
[0065] Comparative Example 5
[0066] The other conditions were the same as those in Example 1, except that Nb was not added and the sintering temperature was increased to 1280°C.
[0067] Comparative Example 6
[0068] The other conditions are the same as those in Example 1, except that copper nitride is not added.
[0069] Comparative Example 7
[0070] The other conditions were the same as those in Example 1, except that ferromanganese nitride was replaced by manganese nitride.
[0071] Comparative Example 8
[0072] The other conditions are the same as those in Example 1, except that no AlSc alloy is added.
[0073] The sintering tests were performed on the designed samples of the embodiment and the comparative example respectively. The powder particle size, composition and sintering temperature plan provided by the embodiment and the comparative example are shown in Table 1.
[0074] Table 1 Particle size, partial composition and sintering temperature of sinterable lightweight high-strength steel powder
[0075]
[0076] According to the designs of the above-mentioned embodiments 1, 2, 3 and comparative examples 1, 2, 3, 4, 5, 6, 7, 8, the designed samples were tested respectively, and the results are shown in Table 2 below.
[0077] Table 2 Preparation conditions and properties of lightweight high-strength steel
[0078]
[0079]
[0080] Conclusion 1: The difference between Examples 1, 2, and 3 is the different sintering temperatures selected during the sintering process. The sintering temperature in Example 2 is lower, and the density is also reduced. It can be found in the metallographic phase that the density of the carbide phase content of the lightweight high-strength steel is lower than that of the lightweight high-strength steel at normal sintering temperature; the sintering temperature in Example 3 is higher. In the metallographic phase, not only the austenite grains grow, but also the austenite grain boundaries undergo grain boundary weakening changes. The matrix also has obvious Widmanstatten structure and black oxides distributed along the grain boundaries. Although the performance of Examples 2 and 3 in terms of density, strength, toughness, etc. is not as good as that of Example 1, they are all improved compared to the prior art and show excellent performance. This shows that the sintering range of the present invention has been greatly expanded.
[0081] Conclusion 2: The difference between Examples 4, 5 and Comparative Example 1 and Example 1 is that the Nb content of each alloy element is determined differently during the mixing process. Comparing Examples 4, 5 and Comparative Example 1 with Example 1, the Nb content gradually increases, the Nb content in Example 4 is relatively low, and the Nb content in Example 5 is relatively high. Comparing the data in the table, as the Nb content gradually increases, the density does not change much, the strength performance gradually increases, but the toughness decreases; the Nb content in Comparative Example 1 is too high, and the strength and other properties in the data are further increased, but the toughness is extremely poor.
[0082] Conclusion 3: Compared with Example 1, Comparative Examples 2, 3, 4, and 5 do not have the addition of Nb element, and the sintering temperature of Example 1 is used as the standard, and the sintering temperature is designed according to the gradient. Comparative Examples 2, 3, 4, and 5 are traditional Fe-Al-Mn-C lightweight steels. Compared with Example 1, Comparative Example 2 has a very low density and no performance; Comparative Example 3 has a slightly lower density, but has a large number of holes and low elongation; Comparative Example 4 has similar density, strength, toughness and other properties to Example 1; Comparative Example 5 has a slightly lower density, but has larger holes inside, lower strength, and extremely low elongation.
[0083] Conclusion 4: Compared with Example 1, Comparative Examples 6, 7, and 8 respectively do not add copper nitride, replace ferromanganese nitride with manganese nitride, and do not add AlSc alloy. Comparative Example 6 does not add an appropriate amount of Cu to promote particle rearrangement and sintering densification, resulting in poor sintering effect and reduced performance. Comparative Example 7 replaces ferromanganese nitride with manganese nitride. Ferromanganese nitride, as a nitrogen additive, can comprehensively improve the various properties of steel. Although manganese nitride can also provide nitrogen, its specific impact on steel performance is different from that of ferromanganese nitride, and the alloy performance is reduced. In Comparative Example 8, the Sc element is not added, and its role in absorbing oxygen, reducing sintering resistance and ensuring alloy uniformity cannot be fully exerted, which reduces the sintering effect and alloy performance.
[0084] Conclusion: From the above results, it can be seen that by adjusting the different sintering parameters of Fe-Al-Mn-C-Nb lightweight steel alloy powder, the density, strength, toughness and other properties of the prepared lightweight high-strength steel material are affected to a certain extent, but by comparison, Example 1 is relatively optimal, but Examples 2 and 3 are improved compared to the prior art and both show excellent performance, which shows that the sintering range of the present invention is greatly expanded.
Claims
1. An easily sintered lightweight high-strength steel powder, characterized in that: The easy-to-sinter lightweight high-strength steel powder has the following components, calculated by mass percentage: C 0.6-2wt.%, Mn 28-32wt.%, Al 9-14wt.%, Nb 0.01-0.6wt.%, Cu: 0.01-0.6wt.%, Sc 0.1-0.5wt.%, N 0.1-0.3wt.%, and the balance is Fe.
2. The easily sintered lightweight high-strength steel powder according to claim 1, characterized in that: The easy-to-sinter lightweight high-strength steel powder is prepared by a gas atomization method.
3. The easily sintered lightweight high-strength steel powder according to claim 1 or 2, characterized in that: The particle size D of the sinterable lightweight high-strength steel powder 10 =3-6μm, D 50 =10-14μm, D 90 =22-30μm.
4. The method for preparing an easily sintered lightweight high-strength steel powder according to any one of claims 1 to 3, characterized in that: According to the designed proportion of the easy-to-sinter lightweight high-strength steel powder, various raw materials are mixed, smelted to obtain high-strength steel alloy liquid, and the temperature is continuously raised to superheat the high-strength steel alloy liquid, and then atomized to obtain lightweight high-strength steel powder.
5. The method for preparing an easily sintered lightweight high-strength steel powder according to claim 4, characterized in that: According to the designed proportion of the easy-to-sinter lightweight high-strength steel powder, carbon powder, pure manganese, pure aluminum, pure niobium and pure iron are prepared, and alloy liquid 1 is obtained by smelting, wherein the carbon powder content of the alloy liquid 1 is 0.6-2wt.%, the pure manganese content is 28-32wt.%, the pure aluminum content is 9-14wt.%, the pure niobium content is 0.01-0.6wt.%, and the balance is pure iron; ferromanganese nitride, copper nitride, pure niobium, aluminum-scandium alloy and pure iron are prepared, and alloy liquid 2 is obtained by smelting, wherein the ferromanganese nitride content is 1-5wt.%, the copper nitride content is 0.1-3wt.%, the pure niobium content is 0.01-0.6wt.%, the aluminum-scandium alloy content is 0.1-1wt.%, and the balance is pure iron; 1 / 3 of the volume of the alloy liquid 1 is taken out, and then the alloy liquid 2 equal to the alloy liquid 1 is taken, poured into the remaining alloy liquid 1, and continued to be refined to form a high-strength steel alloy liquid.
6. The method for preparing an easily sintered lightweight high-strength steel powder according to claim 4 or 5, characterized in that: The refining is carried out under electromagnetic stirring, and the refining time is 0.5-1h.
7. The method for preparing an easily sintered lightweight high-strength steel powder according to claim 4 or 5, characterized in that: After the high-strength steel alloy liquid is superheated to 60-250℃, it is gas-atomized; The pressure of the aerosol treatment is 5-20MPa; The alloy powder obtained after gas atomization treatment is sieved and then dried at 100-120°C for 1-3h to obtain lightweight high-strength steel powder.
8. The use of an easily sintered light-weight high-strength steel powder according to any one of claims 1 to 3, characterized in that: The easy-to-sinter light-weight high-strength steel powder is used as a raw material to prepare light-weight high-strength steel.
9. The use of an easily sintered light-weight high-strength steel powder according to claim 8, characterized in that: The preparation process of the lightweight high-strength steel is as follows: mixing easy-to-sinter lightweight high-strength steel powder with a binder to obtain feed, injection molding the feed to obtain a rough blank, catalytically degreasing the rough blank to obtain a degreased blank, and sintering the degreased blank to obtain lightweight high-strength steel, wherein the sintering temperature is 1160-1250° C. and the sintering time is 5-10 hours.
10. The use of an easily sintered light-weight high-strength steel powder according to claim 9, characterized in that: The binder comprises the following components by mass percentage: 85-89% polyoxymethylene, 3-8% polyethylene, 1-6% ethylene-vinyl acetate copolymer, 1-2% polyethylene wax, 2-7% carnauba wax, 1-3% styrene-acrylonitrile copolymer, and 0.1-1% antioxidant; The injection molding temperature is 170-180°C and the pressure is 80-90MPa; The catalytic degreasing is carried out in an atmosphere of fuming nitric acid, the temperature of the catalytic degreasing is 100-140° C., and the time of the catalytic degreasing is 3-8 hours.